Network coding for system‐level throughput improvement in satellite systems. (25th September 2017) - Alegre‐Godoy, R.; Vázquez‐Castro, M. Ángeles
Summary: In this paper, we introduce 2 designs based on network coding (NC) for system‐level throughput improvement in satellite systems. The first design is applied to the forward downlink of multibeam satellite systems using an adaptive physical layer. In this type of systems, user terminals (UTs) receiving a satellite channel happen to also be able to receive physical links transmitted towards other UTs in other geographical areas. Hence, if UTs were able to tune other physical channels, they could access and decode all such signals. Assuming such multilink reception, the overall system would have an enormous increase of useful throughput, and moreover, multiple paths would become available to every UT. NC can then be naturally used to optimally mix the traffic towards the users through such multiple physical paths. The proposed full design targets multicast applications and achieves throughput improvements of up to the 88% with regard to state‐of‐the‐art schemes. The second design applies to systems where multiple sources transmitting to one or more satellites experience severe packet losses (eg, forward uplink through multiple gateways). Nowadays, system availability is achieved by transmitting the same packets in different spatial channels, ie, using spatial diversity. Using NC to encode the data across users, and introducing novel cognitive elements, the system outage probability can be reduced, thus increasing the throughput. The design is shown to achieve more than one order of magnitude system outage probability advantage for a sufficient number of UTs. Furthermore, a methodology determining the optimal number of transmitting UTs and code rate is derived. Abstract : This paper introduces 2 designs based on network coding for throughput improvement in satellite systems. Design 1 applies to the forward downlink of multibeam satellite systems. Network coding is used to optimally mix the traffic through multiple available physical paths and increase the throughput. Design 2 applies to systems where multiple sources transmitting to one or more satellites experience severe packet losses. Using network coding to encode data across users, the system outage probability can be reduced, thus increasing the throughput.